An analysis of prone to deviant behaviour and coping strategies among school-age athletes - Tatyanina, L.G.; Kirpichnikova, A.V.; Alekseeva, N.D.; Novitskiy, Ya.I. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify tendencies towards deviant behaviour and coping strategies among student athletes involved in cyclic sports and martial arts. Methods and structure of the study. An empirical study was conducted involving 136 students (99 males and 37 females) aged 17–19. All respondents were first-year university students in St Petersburg who were actively involved in sporting activities and participating in competitions. Standardised psychodiagnostic methods were used to collect data: the ‘Predisposition to Deviant Behaviour’ questionnaire and the ‘Coping Behaviour in Stressful Situations’ method. This empirical study examined the propensity for deviant behaviour and coping strategies among student athletes representing cyclic sports and martial arts. Results and conclusions. Significant differences were identified between the groups. Martial arts athletes demonstrate more pronounced non-conformity of attitudes and aggression, a moderate risk of addictive behaviour, and reduced volitional control. In turn, representatives of cyclic sports are characterised by conformity, low aggression, and high volitional control. Athletes in cyclic sports more often resort to problem-focused coping and seeking social support, and less frequently use emotion-focused strategies and avoidance. Combat sports athletes tend to choose emotion-focused coping and avoidance strategies, whilst seeking social support less frequently.